Social workers affecting social policy : an international perspective on policy practice - Gal, John; Weiss-Gal, Idit (JSTOR EBA., 2013)
The goal of this innovative book is to shed light on the role of social workers in social policy formulation in different countries across the globe. The involvement of social workers in this type of activity has been termed 'policy practice' and it refers to activities carried out by social workers as an integral part of their professional work aimed at influencing the formation and adoption of new policies or the modification or preservation of existing ones, whether at the organizational local, national or international levels.